The Revenue Implications of Community Colleges' Reliance on Local Funding - Justin C. Ortagus; Dominique Baker; Kelly Ochs Rosinger; Robert Kelchen; Olivia Morales; Anna Peters; Mitchell Lingo (SAGE Publishing, 2024)
In this study, we leverage national data sources to examine the relationship between community colleges' level of reliance on local funding and their total institutional revenue, focusing specifically on community colleges educating the largest shares of low-income and racially minoritized students. We show that local funding is positively related to total institutional revenue for the pooled sample including all public community colleges, suggesting that local appropriations can supplement state appropriations in ways that benefit a historically underfunded sector of higher education. However, we also show that community colleges' level of reliance on local funding is negatively related to their total institutional revenue for rural community colleges and community colleges serving an above-average share of low-income students. Our findings align with scholarship in K-12 finance, indicating that local appropriations, such as property taxes, may exacerbate inequities facing the institutions serving larger shares of economically disadvantaged students.